Permissioned blockchain approach using open data in healthcare - Cunha, João Carlos Soares (2022)
Digital health records play a key role in the area. However, it is difficult to obtain a unified view of your data, as it is distributed among different providers, spread over several places, and is not integrated. To address these problems, blockchain technology and the openEHR interoperability standard have emerged. Blockchain is a new wave of disruption that has come to redesign interactions that involve any form of exchange of values, with the potential to improve healthcare, bringing a new perspective on security, resilience, and effectiveness of systems. In turn, with the use of openEHR, the standardization of electronic records is guaranteed, offering fine-grained access permissions for stakeholders. In addition to the use of archetypes as a reference to make the templates, where they are integrated to build a module with compatible standards. Based on an open data framework, OpenEHR, and blockchain technology, this paper has conceptualised a proposed two architectures that will be implemented within a Portuguese hospital, at the ICU, to increase and provide support for clinical decision-making, ensuring interoperability between systems, as well as the veracity, privacy and security of the data being used.